2012
DOI: 10.1111/j.1540-4560.2011.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Contesting Privilege with Critical Participatory Action Research

Abstract: The construct of privilege has been undertheorized in the field of psychology. The discipline more commonly examines those who have been disenfranchised, marginalized, and discriminated against. However, psychologists concerned with social issues must also attend to questions of power and privilege. This article uses a collaborative research project with New York City youth and adults called Polling for Justice to engage in a discussion about privilege as it runs through three areas of that work: by design, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 18 publications
(21 reference statements)
0
49
0
Order By: Relevance
“…The approach of engaging an external consultant may have supported the openness of the discussions undertaken and the YA's and adults’ willingness to reflect critically upon their experiences. The role of value‐aligned adults in facilitating processes of knowledge generation is a core consideration for many YPAR researchers . The skill sets suited to address the nuances of participation with youth may be present among a range of practitioners in health and social services, as well as in education and KMb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach of engaging an external consultant may have supported the openness of the discussions undertaken and the YA's and adults’ willingness to reflect critically upon their experiences. The role of value‐aligned adults in facilitating processes of knowledge generation is a core consideration for many YPAR researchers . The skill sets suited to address the nuances of participation with youth may be present among a range of practitioners in health and social services, as well as in education and KMb.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have suggested that a genuine commitment to participatory values implies the continual enactment of anti‐oppressive practices that address individual needs and examine structural conditions that lead to oppression in all stages of knowledge creation and mobilization . Demonstrating such application, Stoudt et al described how self‐reflexive approaches may be applied to situations that involve differentials of power and privilege among youth and adults. Other scholars have addressed the nuances of engaging persons with previous experiences of mental illness and describe the possible accommodations that support work with such individuals .…”
Section: Introductionmentioning
confidence: 99%
“…We selected these factors based on their relationship to aspects of the CoBRAS measure. For example, several of these variables reflect an awareness of privilege, which may impact endorsement of color-blind racial beliefs (McIntosh 2012; Pratto and Stewart 2012;Stoudt et al 2012). People who belong to marginalized groups (e.g., racial minority, Race Soc Probl female, and low income) tend to be more likely than those from privileged or majority groups to hold beliefs that reflect their awareness of institutional racism (Benjamin 1989;Chao 2013).…”
Section: Measures For Sociodemographic Variablesmentioning
confidence: 96%
“…Traditional social science research often tells us to ignore this process of embodied analysis because it may taint research findings and run counter to research goals (Fox, 2015). In PAR work, where participation and action are valued equally to the research, such embodied knowledge is critical to carrying out work that is responsible to collectives and to larger communities (Lykes, 2013;Roberts, 2013;Stoudt, Fox, & Fine, 2012).…”
Section: Analyzing That Which Has No Wordsmentioning
confidence: 99%